Flower abscission and fruit set on table grapes (Vitis vinifera L.): unraveling physiological and molecular mechanisms - Domingos, Sara Nobre Gonçalves (2016)
Doutoramento em Engenharia Agronómica - Instituto Superior de Agronomia - UL